Hospital Safety-Net Burden and Risk for Readmissions and Severe Maternal Morbidity - McKinley, Lilian P.; Wen, Timothy; Gyamfi-Bannerman, Cynthia; Wright, Jason D.; Goffman, Dena; Sheen, Jean-Ju; D'Alton, Mary E.; Friedman, Alexander M. (American Journal of Perinatology, 2020)
Objective This study aimed to analyze whether hospital safety-net burden status is associated with increased risk for severe maternal morbidity (SMM) and postpartum readmissions.Study Design The 2010 to 2014 Nationwide Readmissions Database was utilized for this retrospective cohort study. Hospitals were categorized as high-burden hospitals (25% of hospitals with the highest safety-net burden), medium-burden hospitals (50% of hospitals with intermediate safety-net burden), and low-burden hospitals (25% of hospitals with the lowest safety-net burden) based on the proportions of Medicaid or uninsured patients. Risk for (1) SMM, (2) 60-day postpartum readmissions, and (3) SMM during postpartum readmissions was analyzed. Unadjusted and adjusted log-linear regression models were performed, respectively, for these outcomes with unadjusted risk ratio (RR) and adjusted RR (aRR) as measures of effect. Adjusted models included demographic, hospital, and clinical factors.Results High-burden safety-net status was associated with increased risk for SMM compared with low-burden safety-net status in both unadjusted (RR: 1.51, 95% confidence interval [CI]: 1.50–1.53) and adjusted analyses (aRR: 1.27, 95% CI: 1.25–1.30). High-burden status was also associated with increased risk for readmissions in unadjusted analyses (RR: 1.42, 95% CI: 1.40–1.44), although this risk was attenuated in adjusted analyses (aRR: 1.07, 95% CI: 1.06–1.08). High-burden status was associated with significantly increased risk for readmission for uterine infections, hypertensive diseases of pregnancy, and psychiatric diagnoses. High-burden status was not associated with severe morbidity during readmissions in adjusted or unadjusted analyses (RR: 1.02, 95% CI: 0.98–1.05; aRR: 0.95, 95% CI: 0.92–0.99).Conclusion This study found that high safety-net burden hospitals may be a higher risk setting for obstetric care. Improvement of outcomes in high-burden settings may be important in overall efforts to reduce maternal risk.
Keywords: severe maternal morbidity; safety net; obstetric care; postpartum readmissions; maternal outcomes